(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
With the task of thinking modes of fabulation that include humans and nonhumans, the ethical importance of more-than-human stories for the present moment is affirmed. The essay articulated epistemologies critiques of the one-dimensional closure of reality, pointing to the urgency of reconsidering how we operate language, existence, and the worlds that coexist. Drawing on the concept of radical difference (La Cadena), which understands the existence of ontologically distinct worlds, the essay turned to the play Azira’i and to the Tupinambá Mantle by D. Tukano to observe that the emotional response to the stories presented, and of the irreducible limits of thought, emerges through partial connections, through potentially for regenerative frictions.